1970
DOI: 10.1136/bmj.4.5730.276
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Venous Oxygen Saturation in Relation to Cardiac Output in Myocardial Infarction

Abstract: Summary: Mixed venous oxygen saturations derived from measurement of mixed venous oxygen tension were compared with dye dilution cardiac output determinations in 26 patients with acute myocardial infarction. Mixed venous oxygen saturation was greatly reduced in patients with shock or failure complicating myocardial infarction. The level of oxygen saturation correlated with cardiac output determinations. The measurement of mixed venous oxygen saturation, which is relatively simple and does not require elaborate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
2

Year Published

1993
1993
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(11 citation statements)
references
References 13 publications
0
8
0
2
Order By: Relevance
“…Changes in need of O 2 can therefore only be covered by changes in O 2 extraction. In these patients, SvO 2 is tightly correlated with cardiac output and a drop in SvO 2 is a good and early marker of cardiac deterioration [15]. Correlation between SvO 2 and ScvO 2 was insufficient in patients with heart failure [8] but was reported to be accurate in patients with myocardial infarction [21].…”
Section: Severe Trauma and Hemorrhagic Shockmentioning
confidence: 98%
See 1 more Smart Citation
“…Changes in need of O 2 can therefore only be covered by changes in O 2 extraction. In these patients, SvO 2 is tightly correlated with cardiac output and a drop in SvO 2 is a good and early marker of cardiac deterioration [15]. Correlation between SvO 2 and ScvO 2 was insufficient in patients with heart failure [8] but was reported to be accurate in patients with myocardial infarction [21].…”
Section: Severe Trauma and Hemorrhagic Shockmentioning
confidence: 98%
“…Importance of SvO 2 monitoring has been originally proposed in cardiology patients [15]; however, indications for this monitoring technique have been extended to other areas. One small study demonstrated that maintaining a normal SvO 2 is beneficial in patients with multiple injuries [16].…”
Section: Clinical Application Of Svomentioning
confidence: 99%
“…OER and Sv02 are indicators of oxygen demand-supply relationships in peripheral tissues [11,12], In a disease state in which oxygen delivery is impaired by a decrease in cardiac output, hyp oxemia or anemia, a variety of compensatory mechanisms, such as increased oxygen extrac tion from blood, redistribution of blood How and changes in the oxygen affinity of hemo globin, serve to maintain tissue oxygen con sumption [13], Accordingly, if arterial oxy genation and hemoglobin are uniform, the OER is elevated and the Sv02 is decreased with the reduction of cardiac output. Tissue acid-base balance and tissue oxygen demandsupply relation both express the metabolic state of peripheral tissues dependent on sys temic circulation.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of an intracardiac shunt (i.e. if there is no ventricular septal rupture) these oxygen transport variables may be a good surrogate of cardiac output (CO) [3]. This means, that by just performing two blood gas analyses the cause of the critical condition can be reliably Cardiogenic shock -an inflammatory disease detected within minutes.…”
Section: Still Applicable -The Definition Of Csmentioning
confidence: 99%